CTNI-07. ABTC-1701: PILOT SURGICAL PK STUDY OF BGB324 (BEMCENTINIB) IN RECURRENT GLIOBLASTOMA PATIENTS – RESULTS FROM INTERIM FUTILITY ANALYSIS. (12th November 2021) - Burt Nabors, L; Nakano, Ichiro; Supko, Jeff; Lobbous, Mina; Grossman, Stuart; Ye, Xiaobu; Desideri, Serena; Danda, Neeraja; Fisher, Joy; Strowd, Roy; Walbert, Tobias
Abstract: BACKGROUND: Glioblastoma often can relapse as mesenchymal (MES) tumors, indicating a phenotypic shift during clinical progression. Glioma spheres, when they gain MES phenotypes, develop dependence on AXL for their growth both in vitro and in vivo . The first-in-class orally bioavailable AXL kinase inhibitor bemcentinib has IC50 of 14 nM and is > 100-fold selective for AXL over other kinases. Bemcentinib is currently under evaluation as a monotherapy and in combination with other treatments across various PhII trials in several oncology indications. METHODS: This is an open-label, multicenter, intratumoral pharmacokinetic study of bemcentinib in patients with recurrent glioblastoma for whom a surgical resection is medically indicated. All subjects must have had histological confirmation of glioblastoma by either biopsy or resection that is progressive or recurrent following radiation therapy ± chemotherapy. Intratumoral drug levels were analyzed by LC/MS. RESULTS: A planned analysis after the first 5 patients were enrolled with glioblastoma (4 IDH WT and 1 IDH-mutant), (3m, 2f, median age 57, KPS 80). Bemcentinib concentration in contrast enhancing brain tissue ranged from 3.1 to 43.0 uM with a geometric mean concentration of 11.1 uM (% CV, 132.1). The drug concentration in contrast enhancing tumor tissue exceeded the 1.0 uM threshold in all 5 patients, satisfying the criteria of the protocol to enroll an additional 15 patients into the surgical study. Total drug levels were approximately 2-fold greater in contrast enhancing tissue as compared to tissue from a non-enhancing region of the tumor (geometric mean, 5.8 uM; % CV, 187.7). The mean ratio of the drug concentration in brain tissue to plasma was 25.9 (% CV, 92.7) for contrast enhancing tissue and 13.4 (% CV, 126.8) for non-enhancing tissue. CONCLUSIONS: Bemcentinib readily distributes in brain tumor tissue following oral administration. The study continues to complete accrual for the remaining 15 patients.